THE EFFECTIVENESS OF THE RATING SYSTEM IN INCREASING THE TRAINING MOTIVATION OF SCHOOL-AGE BASKETBALL PLAYERS - Sardorkhon Kuvondikov; Ruxsora Ilxomjanova (Bright Mind Publishing, 2025)
Achieving high results in modern sports depends on the systematic results of long-term training. The athlete's attitude to the training process and his sporting duty largely stems from his training motivation and participation in competitions.
Keywords: Psychology, sports, basketball, physical education, preparation, competition, training, coach, victory, sports psychology.